The Application and Integration of I.C.T. in the Public Sector: an Overall Literature Review Focused on the E.U. Environment - Theodoros Papailias; Konstantinos Papageorgiou; Konstantinos Milioris; Sofia Riakotaki (Brawijaya University, 2022)
The aim of this article is to examine the importance and acceptance of Information and Communication Technologies (I.C.T.) in the public sector. Nowadays, the government, businesses and citizens are going through an era of rapid technological developments which is an excellent opportunity to overcome the reluctance of change and to transform the public sector in such a way that it serves the public interest more efficiently and rapidly, so that it leads to a citizen–friendly society. Through the literature review, an attempt is being made to examine the level of utilization of the offered data information systems and infrastructure and to identify the factors that lead to the adoption or avoidance. Following most recent developments in the European community and CEE countries governments are restructuring their formation to evolve and provide modern digital services. Through a reformation program EU aims to secure an efficient and future proofed e-governance.